2020
DOI: 10.1021/acs.organomet.0c00728
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Cycloplatinated(II) Complexes Bearing Bisphosphine Ligands as Potent Anticancer Agents

Abstract: A family of cationic cycloplatinated­(II) complexes [Pt­(dfppy)­(P^P)]­Cl incorporating bisphosphine ligands was prepared: (dfppy = 2-(2,4-difluorophenyl)­pyridine; P^P = bis­(diphenylphosphino)­methane (1, dppm), 1,2-bis­(diphenylphosphino)­ethane (2, dppe), 1,2-bis­(diphenylphosphino)­benzene (3, dppbz)). The complexes were characterized by means of several analytical and spectroscopic methods. These complexes displayed acceptable stability in biological environments, which was confirmed by NMR, HR ESI-MS, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…the bis-chelated mononuclear complexes have been previously synthesized and characterized by our research group wherein their biological activities were investigated. 57 Herein, after preparation of the precursor complex [PtCl(dfppy)(dmso)], 1 , it is reacted with the diphosphines dppm and dppe with the molar ratio of 2 : 1 ( 1 : diphosphine), giving the binuclear complexes [Pt 2 Cl 2 (dfppy) 2 (μ-P^P)], 3 , dppm, 3a ; dppe, 3b . It is worthy to note that we have previously studied the behavior of the ligand dppbz and observed that it cannot be located as a bridging ligand because of its rigid backbone, which hampers rotation.…”
Section: Resultsmentioning
confidence: 99%
“…the bis-chelated mononuclear complexes have been previously synthesized and characterized by our research group wherein their biological activities were investigated. 57 Herein, after preparation of the precursor complex [PtCl(dfppy)(dmso)], 1 , it is reacted with the diphosphines dppm and dppe with the molar ratio of 2 : 1 ( 1 : diphosphine), giving the binuclear complexes [Pt 2 Cl 2 (dfppy) 2 (μ-P^P)], 3 , dppm, 3a ; dppe, 3b . It is worthy to note that we have previously studied the behavior of the ligand dppbz and observed that it cannot be located as a bridging ligand because of its rigid backbone, which hampers rotation.…”
Section: Resultsmentioning
confidence: 99%
“…The complexes [PtCl(ppy)(dmso)], A , 24,52 [PtCl(dfppy)(dmso)], B , 23,25 and [Pt 2 Cl 2 (ppy) 2 (μ-dppf)], 2a , 26 were prepared by the literature method. All numberings in the characterization and experimental sections are based on the schematic labeling shown in Scheme 2.…”
Section: Methodsmentioning
confidence: 99%
“…21,22 Our recent studies particularly indicate that tuning both phosphine and C^N chelating ligands by changing their substituents in organoplatinum complexes leads to more biologically efficient compounds. 23 To meet this purpose, we designed the syntheses and characterization of a series of cycloplatinated(II) complexes which contain several diphosphinoferrocene and C^N cyclometalated ligands. Also, to extend our studies, density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations were performed on all the complexes and then the biological activities of these complexes including in vitro anticancer activity and their mechanisms, apoptotic and genotoxic effects, and molecular docking simulations were scrutinized.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Shahsavari et al reported the preparation of a series of cycloplatinated (II) complexes bearing different diphosphines and the ligand 2-(2,4-difluorophenyl)pyridine (dfppy) (Figure 13) [66]. They were interested in this ligand due to its chelating nature and the strong Pt-C bond formed, which can provide stability to the complex under physiological conditions to reach the desired target.…”
Section: Platinum Metallodrugsmentioning
confidence: 99%